Psychological Status and Weight‐Related Distress in Overweight or At‐Risk‐for‐Overweight Children - Young‐Hyman, Deborah; Tanofsky‐Kraff, Marian; Yanovski, Susan Z.; Keil, Margaret; Cohen, Marc L.; Peyrot, Mark; Yanovski, Jack A. (Obesity (Silver Spring, Md.), 2006)
Objective: To associate psychological status, weight‐related distress, and weight status during childhood in overweight or at‐risk‐for‐overweight children. Research Methods and Procedures: We associated self‐report of depression, trait anxiety, and weight‐related distress (body size dissatisfaction and weight‐related peer teasing after controlling for the effects of weight) in 164 children (black 35%; age 11.9 ± 2.5 years; girls 51%) who were overweight or at‐high‐risk‐for‐overweight and were not seeking weight loss. Results: Overall, heavier children reported more psychological and weight‐related distress. Black children reported more anxiety and body size dissatisfaction than white children, despite equivalent weights. However, psychological distress was not significantly associated with weight in white children. Girls reported more weight‐related distress than boys. Depression was associated with weight‐related teasing in all predictive models, except in the model using only black subjects. Trait anxiety was associated with report of peer teasing when using all subjects. Depression was also significantly associated with children's report of body size dissatisfaction in models using all subjects, only girls, or white subjects, but not in analyses using only boys or black subjects. For boys peer teasing was associated with body size dissatisfaction. In models including only black children, depression and trait anxiety were not significantly associated with either report of peer teasing or body size dissatisfaction. Discussion: Regardless of race or sex, increasing weight is associated with emotional and weight‐related distress in children. However, associations of psychological status, weight, and weight‐related distress differ for girls and boys, and for black and white children.